Increasing Added Value of Chrysanthemum through Cultivation Improvement in Agro Pudak Lestari Ornamental Plant Farmers Group - I G.B. Udayana; M.Sri Yuliartini; Hanilyn Aguilar Hidalgo; A.A. N. Mayun Wirajaya; I.B. Komang Mahardika; A.A.S Putri Risa; I G.M, Arjana; N. P. Anom Sulistiawati; Luh Kartini; D.K. Tristiana Sukmadewi; N. K. Alit Astiari; Yohanes Parlindungan; I N. Suaria; K.Agung Sudewa; I N. Muliarta; Made Suarta (Asian Journal of Community Services, 2023)
Chrysanthemum (Chrysanthemum sp.) is an ornamental flower commodity that has high economic potential value. Based on the results of initial visits and discussions with the community, it is known that the problems that farmers complain about most are seed procurement problems and leaf rust problems. The aim of this research is to increase the added value of farmers, using extension and training methods. The solutions that will be implemented regarding the problems faced by Farmer Groups are, (1) Increasing knowledge of plant propagation techniques through good and correct seeds and (2) Increasing knowledge about how to control leaf rust disease.